Precopulatory oral sex contact plays an important role in copulatory success in a cryptic desert beetle. Issue 18 (25th August 2021) - Qin, Xinghu; Yang, Jinshu; Ma, Jingchuan; Lock, Thomas Ryan; Wang, Guangjun; Zhang, Zehua
Abstract: Precopulatory courtship plays an essential role in the insemination process and influences postcopulatory behavior between males and females. Male precopulatory oral stimulation of female genitals is rare for invertebrates. Here, we describe an intriguing oral sexual courtship in a cryptic desert beetle Platyope mongolica Faldermann. The males repeatedly contact the female's genitals using their mouths to gain consent to mate. Furthermore, the rate at which males contact the female's genitals relates to the copulation success in a series of observations. However, interference in oral sexual contacts decreased the proportion of successful copulation. Further no‐choice tests found homosexual behavior between males with antenna removed. We report the precopulatory oral sexual behavior and its important role for copulation success in P. mongolica for the first time. These findings highlight the significance of oral sexual courtship in sexual selection. Abstract : Sexual contact commonly occurs among insects (Eberhard, 1994). However, descriptions of precopulatory oral sexual contact in invertebrates remain rare and the evidence for an evolutionary function of precopulatory oral sexual contact is still lacking. We report a precopulatory oral sexual behaviour in Platyope mongolica Faldermann (1835), a darkling beetle typically inhabiting deserts. We provide evidence about its important role in sexual selection.